Operational Risk Aspect of Non-Performing Loans in Microfinance - Anastasia Rasia Rahma Kresiadanti; Maria Ulpah; Rachmad Kresna Sakti (Universitas Pendidikan Ganesha, 2025)
This study examines the influence of operational risk factors on non-performing loans (NPL) and customer group quality in PT Permodalan Nasional Madani (PNM) Mekaar, a microfinance institution under the BRI Ultra Micro Holding. The research addresses the problem of high account officer (AO) turnover and rising operational risks arising from human error, system failure, and external events that may affect PNM’s credit performance. The study aims to analyze how internal processes, human resources, system failures, and external events influence both the quality of customer groups and NPL levels. Using a quantitative approach with a case study design, data were collected from 961 AO respondents across Jakarta, Semarang, and Flores regions through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The findings reveal that human resources, system failure, and external events significantly affect both NPL and customer group quality, whereas internal processes have no significant impact. Moreover, customer group quality significantly influences NPL, implying that stronger social capital and group cohesion reduce credit default risks. These results emphasize the importance of human capital development, system reliability, and external monitoring in managing operational risk and improving lending quality within Indonesia’s ultra-microfinance sector.